New species of water mites of the genus Arrenurus from eastern Turkey (Acari: Hydrachnidia: Arrenuridae) - Smit, H; Erman, O (Swets Zeitlinger Publishers, 2003)
Two new species of the genus Arrenurus are described from Turkey, i.e. Arrenurus oezkani and A. anatolicus. In addition, the taxonomic status of Arrenurus cylindratus latigenitalis Lundblad, 1956 is discussed. It is concluded that this taxon deserves ranking as a separate species.
Keywords: Acari; Hydrachnidia; Arrenurus; new species; Turkey